2012
DOI: 10.1364/oe.20.019148
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-domain OCT with dual illumination and interlaced detection for simultaneous anterior segment and retina imaging

Abstract: We present Fourier-domain/spectral-domain optical coherence tomography (FD/SD-OCT) using a single spectrometer with dual illumination and interlaced detection at 830 nm, which can provide anterior segment and retinal tomograms simultaneously. Two orthogonal polarization components were used so that both parallel and focused beams could simultaneously be made incident on the eye. This configuration with a polarization-separated sample arm enables us to acquire images from the anterior segment and retina effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…An approach with two spectrometers or two scanning channels in the OCT system has been demonstrated to be useful in imaging the anterior segment and the retina. 12, 14 Ruggeri et al 15 demonstrated that the full eye could be imaged with a switchable reference arm. These OCT approaches could be used to obtain axial biometry of the entire eye, but only a portion of the eye was imaged (anterior segment and the retina).…”
Section: Discussionmentioning
confidence: 99%
“…An approach with two spectrometers or two scanning channels in the OCT system has been demonstrated to be useful in imaging the anterior segment and the retina. 12, 14 Ruggeri et al 15 demonstrated that the full eye could be imaged with a switchable reference arm. These OCT approaches could be used to obtain axial biometry of the entire eye, but only a portion of the eye was imaged (anterior segment and the retina).…”
Section: Discussionmentioning
confidence: 99%
“…Although our combined system is able to image the anterior segment including the ciliary muscle, the need to modify the reference arms for compensating sensitivity drop-off and implementation of the shutter may complicate the imaging approach. Further improvement with one system and alterative scanning channels [56] using the wavelength of 1 µm [18] may simplify the approach. Imaging the muscle apex position and width is important in studying the accommodative response.…”
Section: Discussionmentioning
confidence: 99%
“…The cornea is not clear due to the 50% attenuation of the reflected light. A single spectrometer with two illumination sources and interlaced detection has been set up to acquire the anterior segment and retinal tomograms simultaneously [3]. The entire lens was not imaged in that system due to the scan depth being nearly 6.0 mm after the complex artifact removal algorithm was employed.…”
Section: Discussionmentioning
confidence: 99%
“…Because we used a 4096 pixel camera instead of one with 2048 pixels, the imaging depth was increased to more than 12.0 mm, which is long enough to image the entire anterior segment. When imaging the cornea and retina simultaneously with dual-channel SD-OCT systems [3,13], the relative motion between the two regions can be estimated. The disadvantage of our system is the retina obtained from the current study was a small plane line due to the telecentric scanning when measuring the axial length.…”
Section: Discussionmentioning
confidence: 99%